Worlds Beyond Our Own The Search for Habitable Planets - Sengupta, Sujan (Astronomers' Universe, 2015)
This is a book on planets: Solar system planets and dwarf planets. And planets outside our solar system - exoplanets. How did they form? What types of planets are there and what do they have in common? How do they differ? What do we know about their atmospheres - if they have one? What are the conditions for life and on which planets may they be met? And what's the origin of life on Earth and how did it form? You will understand how rare the solar system, the Earth and hence life is. This is also a book on stars. The first and second generation of stars in the Universe. But in particular also on the link between planets and stars - brown dwarfs. Their atmospheric properties and similarities with giant exoplanets. All these fascinating questions will be answered in a non-technical manner. But those of you who want to know a bit more may look up the relevant mathematical relationships in appendices.